Antioxidant Activity and the Potential Mechanism of the Fruit From Ailanthus altissima Swingle - Mo, Ya-nan; Cheng, Feng; Yang, Zhen; Shang, Xiao-fei; Liang, Jian-ping; Shang, Ruo-feng; Hao, Bao-cheng; Wang, Xue-hong; Zhang, Hong-juan; Wali, Ahmidin; Lu, Chun-fang; Liu, Yu (Frontiers in Veterinary Science, 2021)
The fruits of Ailanthus altissima Swingle (AS) possess a variety of pharmacological activities. Its antioxidant activity and the potential mode of action have not yet been investigated. Antioxidant assay in vitro proved AS possessed fairly strong antioxidant capacity. Meanwhile, AS increased the activities of SOD, CAT, GSH-Px and decreased the MDA level compared with the H2O2 group, suggesting it relieved oxidative stress of RAW264.7 cells significantly. Network pharmacology analysis screened the core targets of AS like threonine kinase1 (AKT1), mitogen-activated protein kinase 1(MAPK1), sirtuin-1(SIRT1), mechanistic target of rapamycin kinase (MTOR) and the key pathways involved PI3K-AKT and FoxO signaling pathway. Besides, qRT-PCR revealed AS preconditioning significantly up-regulated the expression level of AKT1, SIRT1, MAPK1, MTOR in model cells, and the effect was related to the regulation of FoxO and PI3K/ AKT signaling pathway. In summary, AS revealed significant antioxidant activity and its potential mechanism was regulating FoxO and PI3K/ AKT signaling pathway.